Bioweathering Potential of Cultivable Fungi Associated with Semi-Arid Surface Microhabitats of Mayan Buildings - Ortega-Morales, Benjamín O.; Narváez-Zapata, José; Reyes-Estebanez, Manuela; Quintana, Patricia; De la Rosa-García, Susana del C.; Bullen, Heather; Gómez-Cornelio, Sergio; Chan-Bacab, Manuel J. (Frontiers in Microbiology, 2016)
Soil and rock surfaces support microbial communities involved in mineral weathering processes. Using selective isolation, fungi were obtained from limestone surfaces of Mayan monuments in the semi-arid climate at Yucatan, Mexico. A total of 101 isolates representing 53 different taxa were studied. Common fungi such as Fusarium, Pestalotiopsis, Trichoderma and Penicillium were associated with surfaces and were, probably derived from airborne spores. In contrast, unusual fungi such as Rosellinia, Annulohypoxylon, and Xylaria were predominantly identified from mycelium particles of biofilm biomass. Simulating oligotrophic conditions, agar amended with CaCO3 was inoculated with fungi to test for carbonate activity. A substantial proportion of fungi, in particular those isolated from mycelium (59%), were capable of solubilizing calcium by means of organic acid release, notably oxalic acid as evidenced by ion chromatography. Contrary to our hypothesis, nutrient level was not a variable influencing the CaCO3 solubilization ability among isolates. Particularly active fungi (Annulohypoxylon stygium, Penicillium oxalicum and Rosellinia sp.) were selected as models for bioweathering experiments with limestone-containing mesocosms to identify if other mineral phases, in addition to oxalates, were linked to bioweathering processes. Fungal biofilms were seen heavily covering the stone surface, while a biomineralized front was also observed at the stone-biofilm interface, where network of hyphae and mycogenic crystals was observed. X-ray diffraction analysis (XRD) identified calcite as the main phase, along with whewellite and wedellite. In addition, lower levels of citrate were detected by Attenuated Total Reflectance-Fourier-Transform Infrared Spectroscopy (ATR-FTIR). Overall, our results suggest that a diverse fungal community is associated with limestone surfaces insemi-arid climates. A subset of this community is geochemically active, excreting organic acids under quasi-oligotrophic conditions, suggesting that the high metabolic cost of exuding organic acids beneficial under nutrient limitation. Oxalic acid release may deteriorate or stabilize limestone surfaces, depending on microclimatic dynamics.